INFLUENCE OF VARIATIONS OF AGILITY TRAINING ON INCREASING AGILITY IN EXTRACURRICULAR FUTSAL PLAYERS OF YAPIM MABAR SMA 2021 - Yoepiter Zega; Amir Supriadi; Novita Novita (Indonesia Sport Journal, 2022)
The purpose of this study was to determine the effect of variations in agility training on increasing agility in extracurricular futsal players at YAPIM Mabar High School in 2021. This research method uses the experimental method. The location was held in the field of SMA YAPIM Mabar, Jalan Mangaan VII Pasar 3, neighborhood 16 Mabar. The time of the study was carried out from July 26, 2021 to August 22, 2021. The population was futsal players at YAPIM Mabar High School in 2021, totaling 12 people. The samples in this study were all futsal players at YAPIM Mabar Senior High School in 2021 with a total sampling technique, the research instrument for data collection with tests and measurements, namely the Shuttle-run test. To see the effect of each dependent variable and independent variable, the t-test statistical calculation was used. From the results of hypothesis testing, namely the effect of variations in agility training on agility, the results obtained tcount = 6.4. Then, this value is compared with the ttable value (6.4 > 2.20), at the level of = 0.05 and dk n-1, (12-1) = 2.20. Thus tcount > ttable so that Ho is rejected and Ha is accepted. The conclusion is that there is an effect of variations in agility training on increasing agility in extracurricular futsal players at YAPIM Mabar High School in 2021.Keywords: Futsal, Agility, Training